Pengaruh Badan Usaha Milik Desa Terhadap Pendapatan Asli Di Desa Sukajadi Kecamatan Bukit Batu Kabupaten Bengkalis - Tomisa, Muhammad Elsa; Syafitri, M. (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2020)
The Village Owned Enterprise was born as a new approach to improving the village economy based on the needs and potential of the village. This research aims to determine the effect of Village-Owned Enterprises on the village’s original income. This research used a sample of 75 respondents from village officials and village institutions. Data collection methods used in this research were interviews, observation, questionnaires and literature study. The data analysis method used is quantitative analysis. The results of this research indicate that there is an influence of Village Owned Enterprises on Village Original Income in Sukajadi Village, Bukit Batu District, Bengkalis Regency.